Respostas
respondido por:
0
a) x +x /2 = 12
2x/ 2 = 12
2x = 12 * 2
2x = 24
x= 12
______________________________________________
b)x/2 + 4x = 15 - (-x-6)
x/2 + 4x = 15 + x + 6
x/2 + 4x = 21 + x
(tira o MMC)
x + 8x = 42 +2x
9x - 2x = 42
7x = 42
x= 6
2x/ 2 = 12
2x = 12 * 2
2x = 24
x= 12
______________________________________________
b)x/2 + 4x = 15 - (-x-6)
x/2 + 4x = 15 + x + 6
x/2 + 4x = 21 + x
(tira o MMC)
x + 8x = 42 +2x
9x - 2x = 42
7x = 42
x= 6
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás